EVALUASI PENGGUNAAN ANTIDIABETIKA PADA ULKUS DIABETIK (STUDI KASUS DI RS PKU MUHAMMADIYAH YOGYAKARTA) - , Recta Olivia Umboro; , Prof. Dr. Djoko Wahyono, SU., Apt ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Diabetic ulcers and gangrene are the most frequent cases of diabetes were hospitalized. Several studies in Indonesia showed that 17-23% mortality rate due to ulcers or gangrene and 15-30% due to amputation. Blood glucose control is an integral factor which is affecting the successful management of diabetic ulcers. Blood glucose control can be done by the management of pharmacologic therapy, either in the form of oral antidiabetics therapy, insulin, or a combination of both. This is a noneksperimental research with descriptive design evaluative and search by a retrospective quantitative data through of the medical records of patients with a T2DM diabetic ulcers diagnosis. This research implemented in PKU Muhammadiyah Yogyakarta hospital period January 2010-December 2011. Data were analyzed with descriptive analysis and chi-square evaluative on the correlation between the type of therapy with blood glucose levels, and the correlation between blood glucose levels with the clinical outcome of patients T2DM diabetic ulcers. The results showed that the pattern of use antidiabetics in patients with T2DM in PKU Muhammadiyah Yogyakarta hospital whom using insulin (46.7%), oral hypoglycemic drugs (OHD) 18.1%, the combination therapy of OHD-OHD (20.5%), the combination therapy of insulin-OHO (13.9%), the combination therapy of insulin-insulin (0.8%). For the type of insulin which is the most used is rapid acting insulin (67.9%), for the OHD is biguanid most used (68.2%). As for the combination therapy which most used OHD-OHD is biguanid-sulfonylurea (94%), the type of combination therapy of insulin-OHD most used is insulinbiguanid, and for the insulin-insulin combination therapy most used is the rapid acting-long acting insulin (100%). The results of chi-square analysis between the type of therapy with blood glucose levels showed that there were significant (p = 0.016), whereas for the chi-square analysis between blood glucose levels with diabetic ulcer clinical outcome suggests that there is a significant relationship (p = 0, 00).